Effects of Adoption of Improved Onion Varieties on Farmers’ Productivity in Kudan Local Government Area of Kaduna State, Nigeria - Issa, Fadlullah Olayiwola; Nti, Catherine (Journal of Environmental and Science Education, 2023)
Farmers’ consistency in adopting improved crop varieties is capable of guaranteeing sustainable development via high productivity and enhanced food security. The study assessed the effects of adoption of Improved Onion Varieties (IOVs) on farmers’ productivity in Kudan Local Government Area (LGA) of Kaduna State, Nigeria. Two-stage sampling procedure was used to select 111 onion farmers from four Wards in the LGA. Structured interview schedule was used to obtain required data. Descriptive statistics (frequency count and percentages), and ANOVA were used to analyse the data. Results shows that the average output before adoption was 3.29 while the mean after adoption was 4.55. ANOVA showed a significant difference between the adopters of improved onion varieties and non-adopters; F(1.109) = 154.91, P<0.001. The major constraint to adoption of IOVs was high cost of improved seeds (=4.81). This paper concludes that the adoption of IOVs has effect on the productivity of onion farmers. The National Agricultural Seed Council should ensure availability of improved seeds by fast-tracking seed multiplication and distribution to farmers so as to increase the sustainable adoption of IOVs.